Penerapan Teknik Relaksasi Napas Dalam dengan Kombinasi Dzikir Asmaul Husna Terhadap Tekanan Darah pada Pasien Hipertensi di RSUD Dr. Soediran Mangun Sumarso Wonogiri - Sri Amalia; Eska Dwi Prajayanti; Sumardi Sumardi (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Hypertension is a chronic condition characterized by an increase in systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90mmHg in the walls of arterial blood vessels. Hypertension rarely causes symptoms so many do not realize that they have suffered from hypertension. This condition needs more attention, as hypertension can cause a variety of chronic diseases such as strokes, heart failure and even death. Efforts to implement hypertension can basically be done through both pharmacological and non-pharmacological therapies. To find out the results of application of Inner Breath Relief Technique with combination of Dzikir Asmaul Husna against blood pressure in hypertensive patients in RSUD Dr. Soediran Mangun Sumarso. This research design uses case study methods with descriptive research modes. Blood pressure test results after application of deep breath relaxation technique with a combination of dzikir asmaul husna at Tn. I 165/98 mmHg whereas at N. S 194/112 mm Hg due to N.S as a control group. There was a change in blood pressure before and after the application of deep breath relief therapy with the combination of dzikir asmaul husna in Mr. I.